(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The task and purpose of scientific research: to form a holistic systemic view of this direction of analytical activity, to assess the current state of its development, and to determine the directions of further scientific research in this area, based on a critical reflection of existing proposals on the content, purpose, goals, objectives, directions, methods and tools for analyzing innovation. The methodology and scientific approaches: analysis and synthesis, critical thinking meaningful. The boundaries of research, the possibility of using the results, the direction of further research: The article analyzes publications on the issues of innovation analysis over the last 10 years of Ukrainian and foreign researchers. Practical value: Development of teaching and methodological support of a new discipline of master’s level of preparation – «Analysis of innovations», improvement of the quality of coursework and diploma papers on the issues of innovation management. The originality / value – the formation of the author’s concept. Conclusions as the main results of research work. The analysis of innovations is an independent direction of economic analysis, a specially organized analytical study of retrospective trends and the current state, problems and prospects for carrying out innovative activities of various economic objects. The main functions of the analysis of innovations are: informational, evaluation, control, motivational, informationprognostic. The main subjects of analysis are: executives and managers, employees, owners (shareholders), investors and lenders, government agencies and the public. It is advisable to isolate innovation types of analysis depending on the object and the subject of analysis by the criterion of temporal orientation, the completeness of the analytical study on the nature of the analytical procedures and their methodologies. The analysis of innovations involves 11 stages of work: resources and expenses of the enterprise for innovation activity; the dynamics of innovation processes in the enterprise and the duration of its individual phases; results and impacts; efficiency and effectiveness; innovative culture and innovative climate; innovative potential; analysis of trends of the development of the market of innovations, perspective analysis of innovative ideas and proposals.